Investigating the maximum resolution of µXRF core scanners: A 1800 year storminess reconstruction from the Outer Hebrides, Scotland, UK. (February 2016) - Orme, Lisa C; Reinhardt, Liam; Jones, Richard T; Charman, Dan J; Croudace, Ian; Dawson, Alastair; Ellis, Michael; Barkwith, Andrew
Micro x-ray fluorescence (µXRF) core scanning is capable of measuring the elemental composition of lake sediment at sub-millimetre resolution, but bioturbation and physical mixing may degrade environmental signals at such fine scales. The aim of this research is to determine the maximum possible resolution at which meaningful environmental signals may be reconstructed from lake sediments using this method. Sediment from a coastal lake in the Outer Hebrides, Scotland, has been analysed using calibrated element measurements to reconstruct storminess since AD 200. We find that a Ca/K ratio in lake-core sediments reflects the presence of fine calcium carbonate shell fragments, a constituent of sand in the catchment that is washed and blown into the lake. Variations in this ratio are significantly correlated with instrumental records of precipitation and low pressures, suggesting it is a proxy for storminess. Furthermore, identification of a c . 60-year cycle supports a climatic influence on Ca/K, as this cycle is frequently identified in reconstructions of the North Atlantic Oscillation and North Atlantic sea-surface temperature. Comparison with weather records at different resolutions and spectral analysis indicate that µXRF data from Loch Hosta can be interpreted at sub-decadal resolutions (equivalent to core depth intervals of 3–5 mm in this location). Therefore, we suggest that sub-centimetre sampling using µXRF core scanning could be beneficial in producing environmental reconstructions in many lake settings where sediments are not varved.